Factors affecting steroidogenesis and luteolysis in ovine and equine corpora lutea - Slough, Teresa Lea, author; Niswender, Gordon, advisor; Bruemmer, Jason, advisor; Nett, Terry, committee member; Burns, Patrick, committee member; Denniston, David, committee member (Colorado State University. Libraries, 2007)
Repeated serial biopsies of luteal tissue were collected from mares (n-5) on days 2 and 5 following ovulation, and on alternating days from day 12 until luteolysis. Messenger RNA levels of steroidogenic acute regulatory protein (StAR); 3β-hydroxysteroid dehydrogenase, Δ5-Δ4 isomerase (3β-HSD); cyclooxygenase-2 (Cox-2); and caspase-3 were measured. The procedure did not affect progesterone production or luteal area. Messenger RNA expression of StAR (p=0.10) and 3β-HSD (p=0.15) decreased between samples obtained on days 12 and 14 and no significant differences in caspase-3 and Cox-2 mRNA levels were detected. A second experiment was conducted to determine if blocking luteal PG production would inhibit luteolysis. An implant containing 0 mg, 3 mg, or 30 mg of indomethacin (indo) was injected into the CL of cycling mares (n=18) on day 9 following ovulation. Half of each treatment group received an i.m. injection of Lutalyse (+ PG) on day 12 (n=3). Decreases in serum concentrations of progesterone were detected in all groups between days 12-13 (p<0.08) and no treatment effect was detected. Thus, no evidence was obtained that inhibition of intraluteal PGF2α synthesis affects luteolysis in the mare. A final experiment was conducted to examine the role of intraluteal PGF2α synthesis during luteolysis in the ewe. On day 9 following heat detection, the CL of ewes with unilateral ovulations (n=20) were treated with an implant containing 0 mg or 10 mg. A final experiment was conducted to examine the role of intraluteal PGF2α synthesis during luteolysis in the ewe. On day 9 following heat detection, one of the following treatments was administered: in ewes with unilateral ovulations (n=20), a CL was treated with an implant containing 0 mg or 10 mg indo. In ewes with bilateral ovulations (n=10), one CL was treated with 0 mg indo and a CL on the opposite ovary was treated with 10 mg indo. On day 12, five ewes from each treatment group received a single i.m. injection of 10 mg Lutalyse. Blood was collected every 4 hours for 24 hours following PG injection. Lutalyse treatment caused a decline in serum concentrations of progesterone within 4 hours (p=0.02), but by 24 hours ewes receiving 10 mg indo + PG had serum concentrations of progesterone that were higher than those receiving 0 mg indo + PG (p=0.04). While CL exposed to PG had lower levels of mRNA encoding StAR and higher levels of mRNA encoding cox-2, indo treatment did not affect mRNA expression. Some results supported the hypothesis that luteal PG production plays a critical role in luteolysis, but the results were not definitive.
Keywords: anatomy and physiology; physiology